ESMO recommendations on microsatellite instability testing for immunotherapy in cancer, and its relationship with PD-1/PD-L1 expression and tumour mutational burden: a systematic review-based approach. (6th May 2019) - Luchini, C; Bibeau, F; Ligtenberg, M J L; Singh, N; Nottegar, A; Bosse, T; Miller, R; Riaz, N; Douillard, J -Y; Andre, F; Scarpa, A
Abstract: Background: Cancers with a defective DNA mismatch repair (dMMR) system contain thousands of mutations most frequently located in monomorphic microsatellites and are thereby defined as having microsatellite instability (MSI). Therefore, MSI is a marker of dMMR. MSI/dMMR can be identified using immunohistochemistry to detect loss of MMR proteins and/or molecular tests to show microsatellite alterations. Together with tumour mutational burden (TMB) and PD-1/PD-L1 expression, it plays a role as a predictive biomarker for immunotherapy. Methods: To define best practices to implement the detection of dMMR tumours in clinical practice, the ESMO Translational Research and Precision Medicine Working Group launched a collaborative project, based on a systematic review-approach, to generate consensus recommendations on the: (i) definitions related to the concept of MSI/dMMR; (ii) methods of MSI/dMMR testing and (iii) relationships between MSI, TMB and PD-1/PD-L1 expression. Results: The MSI-related definitions, for which a consensus frame-work was used to establish definitions, included: 'microsatellites', 'MSI', 'DNA mismatch repair' and 'features of MSI tumour'. This consensus also provides recommendations on MSI testing; immunohistochemistry for the mismatch repair proteins MLH1, MSH2, MSH6 and PMS2 represents the first action to assess MSI/dMMR (consensus with strong agreement); the second method of MSI/dMMR testing is represented by polymerase chain reaction (PCR)-based assessment of microsatellite alterations using five microsatellite markers including at least BAT-25 and BAT-26 (strong agreement). Next-generation sequencing, coupling MSI and TMB analysis, may represent a decisive tool for selecting patients for immunotherapy, for common or rare cancers not belonging to the spectrum of Lynch syndrome (very strong agreement). The relationships between MSI, TMB and PD-1/PD-L1 expression are complex, and differ according to tumour types. Conclusions: This ESMO initiative is a response to the urgent questions raised by the growing success of immunotherapy and provides also important insights on the relationships between MSI, TMB and PD-1/PD-L1.